Thermodynamic and economic analyses of a Brazilian natural gas thermal power plant - Branco, Fabiano P.; Dib, Fernando H.; Takaki, Alessandro T.; Maia, Cassio R. M.; Ramos, Ricardo A. V. (Natl Technical Univ Athens, 2006)
In this work, thermodynamic and economic analyses are applied to a Brazilian thermal power plant operating with natural gas. The analyses are performed in two cases: the current configuration and the future configuration. The current configuration is constituted by four gas turbines which operate in open cycle. The future configuration is obtained by a plant repowering by addition of four recovery boilers, two steam turbines and others equipment and accessories necessary to operate in combined cycle. In order to obtain the performance parameters, energetic and exergetic analyses for each case considered are carried out. on the other hand, thermoeconomic analysis provides means to evaluate the influences of the capital and fuel costs in the composition of the electricity costs. Techniques of investment analysis are also applied to the new configuration and from the results obtained it is possible to verify the advantages of the modifications.
Keywords: energy; exergy; thermoeconomy; thermal power plant; natural gas